Epidemiology and clinic of Oholera 1970 in the Astrakhan region - G. A. Kharchenko; O. G. Kimirilova; V. S. Burkin (Детские инфекции (Москва))
The prognosis for cholera in the world remains unfavorable. There is a high incidence of cholera in the countries of Africa and the Caribbean, which does not exclude the possibility of importation of the infection to Russia and the recurrence of the cholera epidemic.The aim of the study was to establish the clinical and epidemiological characteristics of cholera Eltor in the Astrakhan region in 1970.A retrospective study the information sources were the medical history and results of laboratory examination of 1 246 patients with cholera in 1970 treated in the Regional infectious hospital and redeveloped during the epidemic hospitals of Astrakhan.The duration of a cholera epidemic on the territory of Astrakhan region, with mass cases of the disease, accounted for 55.0 ± 15.8 days. The infection rate of cholera of inhabitants of Astrakhan were lower compared to living in rural areas. Water infected with Cholera Vibrio was the main factor of pathogen transmission. The predominant clinical forms of cholera were mild and moderate (72%), the proportion of severe and algid forms was 28% of the total number of patients.The maximum development of cholera epidemic reached in the delta areas of Astrakhan region. The factor of the pathogen transmission was water, which contributed to the rapid increase in the number of patients. With a total number of severe and algid forms of cholera 350 (28%), in 35 (10%) patients, the disease was fatal.